Whole-genome sequencing investigation of animal-skin-drum-associated UK anthrax cases reveals evidence of mixed populations and relatedness to a US case. Issue 5 (7th November 2015) - Pullan, Steven T.; Pearson, Talima R.; Latham, Jennie; Mason, Joanne; Atkinson, Barry; Silman, Nigel J.; Marston, Chung K.; Sahl, Jason W.; Birdsell, Dawn; Hoffmaster, Alex R.; Keim, Paul; Vipond, Richard
Abstract : There have been two anthrax cases affecting people that played and/or made animal-skin drums in the UK during the last 10 years, with single fatal occurrences in Scotland in 2006 and London in 2008. Investigations by the Health Protection Agency (now Public Health England) employing multi-locus-variable number tandem repeat analysis had previously linked the clinical cases to spores associated with animal skins and drums the patients had been in contact with. In this study, whole-genome sequencing of 23 Bacillus anthracis isolates harvested during the investigations was performed. High-quality draft assemblies of these genomes provided greater characterization of the B. anthracis strains present and placed them all upon a new branch of the global phylogeny. Although closely related, the clinical isolates from the two events, and another isolated from a drum-skin-associated case in New York in 2006, were distinct from each other. Multiple distinct genotypes were found during both investigations, implying either multiple contamination events or a single heterogeneous contamination. One environmental isolate from the Scottish incident was more closely related to London isolates than to the other Scottish isolates. As B. anthracis of this subgroup was present at both geographically and temporally distinct events, it may be more widespread at the source of contamination. All isolates were distinct from currently characterized West African strains, despite this being the likely origin of the drums and hides, therefore adding to our knowledge of B. anthracis diversity in the region.